Analysis of gaze characteristics with eye tracking in elite athletes: A pilot study [Göz hareketleri takibi ile elit sporcularda baki{dotless}ş karakteristikleri analizi: Pilot çali{dotless}şma] - (:unkn) unknown (Institute of Electrical and Electronics Engineers Inc., 2003)
Eye movements are essential for natural vision. Eye tracking technology is being used in research in many disciplines to examine the differences in the visual attention of experts and novices. Eye tracking research in sports focuses in the performance of athletes and its relation with perceptual processes. The aim of these studies relies in training the visual behavior of the athletes and to arrange trainings to increase their performance. In this study, the elite group is the Karate-Do players, and the aim is to extract their visual behavioral characteristics and patterns, to explore their gaze strategies, and the differences in their perception, attention and judgement. The experimental paradigm is a Kata and Bunkai video montage from World championships, where the elite athletes are asked to follow the techniques of the players, and the controls, which are interested in Karate-Do but not ever tried it, are asked to follow the movements of the players. During this time the eye tracking is done, and average fixation times, and dwell time in each area of interest have been calculated, and a significant difference between the two groups has been detected. The elite athletes have less fixation counts but longer fixation time compared to controls. So the professionals are not only extracting information from the center, but also from the peripheral areas. This finding is in agreement with the eye tracking literature. Future works will rely in investigating Karate-Do players from varying Karate-Do branches in groupwise comparison. © 2014 IEEE.